2001
DOI: 10.1667/0033-7587(2001)155[0288:rwapem]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Radioimmunotherapy with Alpha-Particle Emitters: Microdosimetry of Cells with a Heterogeneous Antigen Expression and with Various Diameters of Cells and Nuclei

Abstract: Intercellular variations in the level of antigen expression and in cellular and nuclear radii were taken into account in a model used to estimate cell survival for an in vitro experiment with antibodies containing alpha-particle emitters that target the cell surface. Using measured variations in these characteristics for cells of two human cancer cell lines, the model gave results for cell survival and the fundamental parameter of radiation sensitivity, z(0), that differ substantially from those obtained using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 13 publications
1
39
1
Order By: Relevance
“…This SD was, in some cases, slightly higher than theoretic estimations. However, previous studies observed relatively high biologic variability in the number of antigens present at the surface of tumor cells (26,27), possibly explaining the discrepancy between our theoretic estimations and experimental measurements.…”
Section: Uncertaintiescontrasting
confidence: 81%
“…This SD was, in some cases, slightly higher than theoretic estimations. However, previous studies observed relatively high biologic variability in the number of antigens present at the surface of tumor cells (26,27), possibly explaining the discrepancy between our theoretic estimations and experimental measurements.…”
Section: Uncertaintiescontrasting
confidence: 81%
“…The reliability of this approach stems from its use of emitted radiations to ascertain the distribution. Other experimental techniques, such as flow cytometry (24,25), can also be used to derive the distribution. Because of the ubiquitous presence of LN distributions, many investigators studying radiobiologic responses to radiopharmaceuticals and other radiochemicals may find this distribution useful to fold into their dose-response models (8,24,26).…”
Section: Discussionmentioning
confidence: 99%
“…Targeting of single signaling components often does not result in optimal cytotoxicity. This is partly due to non-uniform distributions of target antigen expression in cell populations, which may limit the ability to target all cells with toxic levels of therapeutic agents [14][15][16]. Therefore, developing therapeutic approaches that concomitantly target multiple signaling components of the EGFR and PI3K pathways might significantly sensitise prostate cancer cells to radiotherapy and improve treatment outcome.…”
mentioning
confidence: 99%